Clinical grade manufacture of 3D printed patient specific biodegradable devices for pediatric airway support. (October 2022) - Ramaraju, Harsha; Landry, April M.; Sashidharan, Subhadra; Shetty, Abhishek; Crotts, Sarah J.; Maher, Kevin O.; Goudy, Steven L.; Hollister, Scott J.
Abstract: Implantable patient-specific devices are the next frontier of personalized medicine, positioned to improve the quality of care across multiple clinical disciplines. Translation of patient-specific devices requires time- and cost-effective processes to design, verify and validate in adherence to FDA guidance for medical device manufacture. In this study, we present a generalized strategy for selective laser sintering (SLS) of patient-specific medical devices following the prescribed guidance for additive manufacturing of medical devices issued by the FDA in 2018. We contextualize this process for manufacturing an Airway Support Device, a life-saving tracheal and bronchial implant restoring airway patency for pediatric patients diagnosed with tracheobronchomalacia and exhibiting partial or complete airway collapse. The process covers image-based modeling, design inputs, design verification, material inputs and verification, device verification, and device validation, including clinical results. We demonstrate how design and material assessment lead to verified Airway Support Devices that achieve desired airway patency and reduction in required Positive End-Expiratory Pressure (PEEP) after patient implantation. We propose this process as a template for general quality control of patient-specific, 3D printed implants. Graphical abstract: Image 1